Analisis Segmentasi Hypermarket dikota Palembang - Ahmad Nazaruddin; Islahuddin Daud; Eko Fitrianto (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
Heterogeneity of consumers make the company needs to adapt to serve optimally. Grouping customers based on similar characteristics are the company's efforts to win the competition. This study attempts to categorize the hypermarket’s visitors in the city of Palembang. This study attempts to categorize visitors of hypermarket in the city of Palembang. There are 200 people was participated in the study which is the visitor one of the 3 different hypermarkets. There are 3 brand of hypermarket was studied, namely: Carrefour, Hypermart and Giant. To obtain consumer clusters, cluster analysis selected for the analysis technique. Results from this study is there are 3 segments (clusters), and each segment has different characteristics. Segment 2 has the greatest number of members and they importance of all variable items compared to two other segments. By knowing the market segment, the company can develop specific marketing strategies to win competition